Teknolite Lumino Tech Pvt. Ltd. Summer Internship - Jain, Garvit (ATLAS SkillTech University, 2024)
Teknovision Private Limited was formed in Mumbai in the year of 1985 for manufacturing DC Tube lights and inverters for Buses and Trains. Our Inverters and Fittings for buses got approval from almost all city and state transport undertakings such as DTC Delhi, BEST Mumbai, AMTS Ahmedabad and Indian Railways. Our fittings are being used for buses for export to other countries.
Project Report on Teknolite Lumino Tech Pvt. Ltd. Summer Internship (2022-24) Under the Guidance of Prof. Prem Colaco
Keywords: Teknovision; Vision